TYPES OF WAX, CHEMICAL COMPOSITION AND PROPERTIES - Jamolov R. Q.; Ro’zmatova N.; Sobirova S. (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract: Beeswax wax products are obtained by processing in apiaries and wax melting and boiling plants. In beehives, it is obtained by melting wax in the sun in a wax melter or by boiling the wax and wax pieces in water, and in wax factories, the residues and wax left as waste from wax melting in beehives are pressed under high pressure or driven under high pressure and with gasoline. Wax products are divided into the following types: wax waste, wax waste after melting wax, apiary waste and factory waste. In addition, a waxy substance (propolis) is also separated as a separate wax product. Wax products are obtained from low-quality, blackened, moldy, contaminated wax from beehives and wax shavings from bee nests, as well as wax shavings that have been cut off during honey extraction.